2020
DOI: 10.1177/2050312120926437
|View full text |Cite
|
Sign up to set email alerts
|

Study on drug use pattern in primary healthcare centers of Kathmandu valley

Abstract: Background: The basic health service is a fundamental right of every citizen. Appropriate use of medicine is an essential component for the quality of health. Drug use evaluation is a systematic and criteria-based drug evaluation, which ensures the appropriate use of the drug. The purpose of this study was to analyze the drug use situation in primary healthcare centers of Kathmandu valley. Methodology: A cross-sectional descriptive study was performed in all primary healthcare centers of Kathmandu valley. Six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 15 publications
1
15
3
1
Order By: Relevance
“…Studies showed that 90–95% of medicines are prescribed in brand name in tertiary care health facilities where patients have the choice to choose generic alternative; whereas, only around 40% of medicines were found to be prescribed in brand name in governmental healthcare facilities where the government freely supplies the medication, and generally, patients do not have to purchase out of pocket. 7 , 8 , 30 , 32 …”
Section: Scenario Of Generic Medicine and Generic Prescribing In Nepalmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies showed that 90–95% of medicines are prescribed in brand name in tertiary care health facilities where patients have the choice to choose generic alternative; whereas, only around 40% of medicines were found to be prescribed in brand name in governmental healthcare facilities where the government freely supplies the medication, and generally, patients do not have to purchase out of pocket. 7 , 8 , 30 , 32 …”
Section: Scenario Of Generic Medicine and Generic Prescribing In Nepalmentioning
confidence: 99%
“… 31 On the other hand, Nepalese customers have low health literacy, 46 and do not have sufficient knowledge and awareness of generic medicines. They even do not clearly understand the medical terminologies, names of medications being prescribed, dose and administration schedule of prescribed medicines 7 ; thus, they rely entirely on the prescribers, pharmacists, nurses, and other healthcare professionals (HCPs), regardless of whether the medicines can be substituted by generic alternative or not. They do not have many options to choose medications themselves, highlighting the necessity of generic medicine intervention at both the HCPs’ and general population’s levels.…”
Section: Hurdles To Generic Medicine Usage and Generic Prescribing In...mentioning
confidence: 99%
See 3 more Smart Citations